DESKRIPSI KETERAMPILAN ASESMEN DAN STIMULASI HOTs GURU SEKOLAH DASAR: STUDI KUALITATIF - Diana, Diana; Kartika, Aniva (Program Studi S1 Psikologi, 2024)
In elementary school learning process, teacher skill in conducting assessment and stimulation determined the extent of student’s thinking processes in classroom. The results of the assessment were used to determine learning stimulation. The qualitative study in this research aims to obtain an overview of teacher skills in assessing and stimulating student abilities in the classroom. Data was obtained through Focus Group Discussions with teacher representatives from each grade level. The results of the research show that the implementation of assessments carried out by elementary school teachers includes: asking questions about students and their surroundings, giving tests with easy to difficult questions, making observations during learning, and reporting student obstacles and progress. Furthermore, findings on activity stimulation include (1) developing counting, writing, and reading abilities; (2) providing games, cross-field projects, and (3) providing trigger questions to build concepts. Stimulation activities still involve the cognitive demands of remembering and building concepts. Therefore, it is necessary to develop teacher skills in developing activities that encourage students' thinking processes at a higher level, namely strategic and broader thinking.